Research progress on the synergistic regulation of MYB transcription factor-mediated developmental plasticity and stress responses in rice - Peng, Wenyan; Zhang, Yi; Xie, Hongjun; Yu, Yinghong; Zhu, Mingdong (Frontiers in Plant Science, 2025)
As a global staple crop, rice production is seriously threatened by biotic and abiotic stresses. OsMYB, which is a core transcriptional regulator in plants, mediates key processes, including secondary metabolism, organ development, and stress responses. In this paper, we systematically describe the mechanisms underlying the synergistic effects of OsMYB family members on developmental plasticity and stress adaptations. Specifically, 1R-MYB transcription factors mainly regulate metabolism and yield formation, R2R3-MYB transcription factors mainly regulate organ development and stress resistance through the bidirectional modulation of the antioxidant system and lignin synthesis, 3R-MYB transcription factors primarily affect cell cycle regulation, and 4R-MYB transcription factors have functions that remain to be characterized. Further elucidating OsMYB-mediated molecular networks may lead to new strategies for developing stress-resistant and high-yielding rice varieties, with positive implications for sustainable agricultural development.